Show me the money : how to determine ROI in people, projects, and programs - Phillips, Jack J., 1945- (Berrett-Koehler Publishers, 2007)
From IT to HR, from boardroom to shop floor, increased accountability for achieving high-value results for new initiatives is the norm in every organization. The Phillips', the world's leading experts on ROI strategy, distill their years of experience and research into proven tools for determining the value of any project before, during, and after implementation. They present a comprehensive method for measuring the hard-to-measure, and placing monetary value on the hard-to-value. They even show how to measure and place value on intangible qualities like leadership, creativity, customer loyalty, employee engagement, and more. Developed in an easy-to-read format and fortified with case studies, checklists, tips, and tools, this work clarifies and resolves the mystery surrounding the allocation of monetary value. It gives change agents everything they need to provid e detailed evaluations of the potential and actual financial ben efits of any project or program.